LOCAL HISTORY OF MUSLIM COMMUNITIES AT THE WATERSIDE OF RANGSIT CANAL, AMPHOE KHLONGLUANG, PATHUMTHANI PROVINCE : IDENTITY AND ADJUSTMENT - Boonyasathit, Wannaporn; Yuangngen, Natthaporn; Sinnang, Panlamon; Kotchawan, Anuwat (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2025)
This Article aimed to study 1) To explore the historical development of Muslim communities at the waterside of Rangsit Canal, Amphoe Khlongluang, Pathumthani; 2) To study the identities of the Muslim people residing in the area; and, 3) To analyze the adjustment and identity maintenance of the Muslim groups since 1890. The research was conducted by collections of evidence, including related documents from primary and secondary sources as well as field studies.; 1) Rangsit area was a rain forest in flood plain. There were settlements scattered around the riverfront. This area was called “Thung Luang Rangsit.” During 1887-1897, the government began to develop the area into a large rice field for mass production, aiming to export the crop overseas under the name “Rangsit Project.” Consequently, the project attracted many people from various ethnic groups to settle in the area, ranging from capitalists, rice field owners, laborers, and land tenants. There were diverse groups such as the Chinese, Mon, Isan (Laos), and Muslim people. There were four Muslim communities settled in the Rangsit riverfront area. They had gathered together and built a community mosque to fulfill the purpose of religious activities and established the community administrative center; 2) The identities of the Muslims in the area consisted of the identity interrelated with Islam faith, which was expressed through religious activities, daily routine culture, dressing, food and annual festivals, and the identity interrelated with history, which was the Malay language usage in Kaew Nimit and Allala Muslim communities, activities strengthening relations between different mosques, and the Day of Ashura activity; 3) Since the establishment, all four Muslim communities have placed great emphasis on the education for youth development in both religious and academic courses. Over time, Muslims have been adjusting themselves to thrive and create their own social space by cultivating the beliefs of a good way of life according to Islamic precepts through various educational programs.